Digital Strategy for MSMEs: Marketing Optimization of Woven Bags - Oki Dermawan; Amara Silvi Cardona; Elfa Diana; Suci Rahmatu Wahidah (Communautaire: Journal of Community Service, 2024)
This research aims to explore and understand how digital literacy and online marketing strategies can be effectively implemented to empower Micro, Small, and Medium Enterprises (MSMEs) in Budi Lestari Village. The main focus of this study is to identify the obstacles faced by MSME actors in utilizing digital technology, as well as evaluate the impact of digital marketing training on increasing their competitiveness and business growth. The research method used is a qualitative approach with case studies, where data is collected through in-depth interviews, participatory observations, and documentation. The results of the study show that after the training, there is a significant increase in the understanding and skills of MSME actors related to digital marketing, which has a direct impact on increasing turnover and market expansion. The implication of this study is the need to continuously increase digital literacy among MSME actors in rural areas to support the sustainability and growth of their businesses in facing the challenges of globalization.